Women Are Survivors: Public Services Announcements on Violence Against Women in Latin America. (May 2023) - Mensa, Marta; Grow, Jean M.
This study considers the role that public service announcements (PSAs) play in addressing violence against women (VAW) in Latin America. Using content analysis, the study examines 407 PSAs about VAW from 20 Latin American countries. The results show that 62.3% of the PSAs encourage bystanders to denounce violence while portraying women as victims in 48.8% of the PSAs. However, 71.7% of PSAs did not include a helpline or how to report the crime, only 11.8% of the PSAs have non-narrative, or factual information, about VAW, and just 6.4% engage in compelling narrative messaging or storytelling.